2004
DOI: 10.1124/jpet.103.062091
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Ethinylestradiol Glucuronide and Ethinylestradiol Sulfate by the Multidrug Resistance Proteins MRP1, MRP2, and MRP3

Abstract: Ethinylestradiol (EE) is one of the key constituents of oral contraceptives. Major metabolites of EE in humans are the glucuronide and sulfate conjugates, EE-3-O-glucuronide (EE-G) and EE-3-O-sulfate (EE-S). In the present study, transport of EE-G and EE-S by the human multidrug resistance proteins MRP1, MRP2, and MRP3 was investigated using inside-out membrane vesicles, isolated from Sf9 cells expressing human MRP1, MRP2, or MRP3. Vesicular uptake studies showed that EE-G was not a substrate for MRP1, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 37 publications
4
63
0
1
Order By: Relevance
“…Therefore, the clinical significance of drugdrug interactions through inhibition of BCRP by diclofenac needs to be studied in patients. Using inside-out plasma membrane vesicles, extensive studies on the complex modulation (stimulation and/or inhibition) of MRP2/ Mrp2-mediated transport of various anionic compounds have been performed (Bakos et al, 2000;Bodo et al, 2003;Zelcer et al, 2003;Chu et al, 2004;Gerk et al, 2004Gerk et al, , 2007. Transport studies with estradiol-17␤-glucuronide (E 2 17␤G) revealed that E 2 17␤G can stimulate its own transport by MRP2 (Bodo et al, 2003;Zelcer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the clinical significance of drugdrug interactions through inhibition of BCRP by diclofenac needs to be studied in patients. Using inside-out plasma membrane vesicles, extensive studies on the complex modulation (stimulation and/or inhibition) of MRP2/ Mrp2-mediated transport of various anionic compounds have been performed (Bakos et al, 2000;Bodo et al, 2003;Zelcer et al, 2003;Chu et al, 2004;Gerk et al, 2004Gerk et al, , 2007. Transport studies with estradiol-17␤-glucuronide (E 2 17␤G) revealed that E 2 17␤G can stimulate its own transport by MRP2 (Bodo et al, 2003;Zelcer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus a structurally diverse array of compounds, including cannabinoid type 1 (CB1) receptor antagonists (e.g., rimonabant), ethinyl estradiol conjugates, sulfinpyrazone, indomethacin, and chalcogenopyrylium dyes have been reported to modulate organic anion transport by MRP2 (and MRP3) in a complex fashion (Bakos et al, 2000;Bodo et al, 2003;Zelcer et al, 2003;Chu et al, 2004;Gerk et al, 2004;Wittgen et al, 2011;Myette et al, 2013). To explain the biphasic response to some modulators, it has been proposed that the transporter contains both a transport site and an allosteric modulatory site whereby the modulator stimulates the transporter allosterically at low probe (E 2 17bG) concentrations and competes for the E 2 17bG binding site at higher concentrations Bodo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al (2004) have identified ethinylestradiol glucuronide as a higher affinity substrate for ABCC3 than ABCC2. Further evidence implicating Abcc3 as the major transporter of glucuronide conjugates stems from studies in Abcc3 knockout mice, which exhibit significant hepatic retention of acetaminophen-glucuronide compared with wild-type animals without alterations to Abcc2 protein levels (Manautou et al, 2005).…”
Section: Ezetimibe Disposition Is Altered In Experimental Nashmentioning
confidence: 99%